LA TEORÍA DEL CONTEXTO DE T. VAN DIJK COMO PROYECTO ANALÍTICO DERIVADO DEL PRAGMATISMO PEIRCIANO: UN APORTE A LA COMPRENSIÓN SEMIÓTICA DEL DISCURSO - Beltramin, Jorge Brower (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2009)
The objective of this article is to develop a theoretical approach about the context. In such sense, we set out the conceptual contributions in relation to the conditions of discursive production proposed by Teun van Dijk from Pragmatic Epistemology tradition.The perspective of this linguist allows open us towards a theoretical formalization of the situation in which the discourses are generated, exposing a perspective that explains the discursive phenomenon in its social dimension, irreplaceable for the analytical work on any type of discourse. In this way, firstly we raised an elaboration of significant knowledge, and later we delimit and select those conceptual elements that give form to the frame that we call context, using as central theoretical source the works of van Dijk and others authors of interdisciplinary reach whose contributions can to be incorporated to any theory and methodology conceived to give account of the structural organization of the speech.